2010
DOI: 10.1007/s00132-010-1613-5
|View full text |Cite
|
Sign up to set email alerts
|

Fehlermöglichkeiten und Interpretationsprobleme der Osteodensitometrie

Abstract: The clinical relevance of osteoporosis as a frequent systemic skeletal disease is to be found in fractures and their consequences. For prevention of these disease manifestations great importance must be attached to a safest possible diagnosis even before the occurrence of the first fracture and osteodensitometry is a well established technique for this purpose. Among the different measurement procedures DXA (dual-energy X-ray absorptiometry) has become the gold standard worldwide. This method is seen as very r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…DXA should be cautiously interpreted, taking into consideration all potential factors that could either falsely elevate or diminish bone density [ 23 ]. Scholz et al [ 24 ] identified potential sources of error and risks in the interpretation of bone densitometry. In a study on the prevalence of DXA interpretation errors, technical errors were identified in 90% of patients and 42% were major errors (defined as incorrect information that could potentially lead to inappropriate care decisions for the patient) [ 25 ].…”
Section: Osteoporosis Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…DXA should be cautiously interpreted, taking into consideration all potential factors that could either falsely elevate or diminish bone density [ 23 ]. Scholz et al [ 24 ] identified potential sources of error and risks in the interpretation of bone densitometry. In a study on the prevalence of DXA interpretation errors, technical errors were identified in 90% of patients and 42% were major errors (defined as incorrect information that could potentially lead to inappropriate care decisions for the patient) [ 25 ].…”
Section: Osteoporosis Assessmentmentioning
confidence: 99%
“…Because DXA measures BMD in a 2-dimensional image, volumetric BMD (g/cm3) is underestimated in short-stature children and overestimated in tall children. Errors in DXA measurements are also common in adults and can be categorized as patient positioning, data analysis, artifacts, and/or demographics [ 24 ].…”
Section: Osteoporosis Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Knochendichte ist einer der wichtigsten Parameter zur Erfassung möglicher struktureller Veränderungen innerhalb des Knochens und daher auch obligater Bestandteil der Diagnostik und Verlaufskontrolle der Osteoporose (13). Verschiedene Studien zeigten einen negativen Zusammenhang zwischen einer verminderten Knochendichte der Hüfte und der Lang -lebigkeit verschiedener Hüftendoprothesentypen (14)(15)(16).…”
Section: Introductionunclassified